2020
DOI: 10.1038/s41598-020-68168-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between radiation doses to heart substructures and radiation pneumonitis in patients with thymic epithelial tumors

Abstract: Radiation doses to the heart are potentially high in patients undergoing radiotherapy for thymoma or thymic carcinoma because of their origin site and propensity for pericardial invasion. We investigated potential relationships between radiation pneumonitis (Rp) and the dosimetric parameters of lung and heart substructures in patients with thymic epithelial tumors. this retrospective study included 70 consecutive patients who received definitive or postoperative radiotherapy at a median dose of 58.3 Gy. Heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Although heart dose may potentially be a surrogate for lung dose, previous studies have suggested a role for heart dose in the development of pneumonitis. 26 , 32 , 33 , 34 Our study detected a role for heart dosimetric parameters including MHD with a cut point of 10 Gy similar to a similar recently published case series which identified an MHD cut point of 5 Gy. 26 Similarly, we also found that increased cardiac dose metrics including MHD and V40 were correlated with increased risk of death corresponding to a Mayo Clinic case series, which showed worse OS with higher cardiac dose, as well as a secondary analysis of Radiation Therapy Oncology Group (RTOG) 0617, which showed certain cardiac dosimetry metrics corresponded with worse OS.…”
Section: Discussionsupporting
confidence: 87%
“…Although heart dose may potentially be a surrogate for lung dose, previous studies have suggested a role for heart dose in the development of pneumonitis. 26 , 32 , 33 , 34 Our study detected a role for heart dosimetric parameters including MHD with a cut point of 10 Gy similar to a similar recently published case series which identified an MHD cut point of 5 Gy. 26 Similarly, we also found that increased cardiac dose metrics including MHD and V40 were correlated with increased risk of death corresponding to a Mayo Clinic case series, which showed worse OS with higher cardiac dose, as well as a secondary analysis of Radiation Therapy Oncology Group (RTOG) 0617, which showed certain cardiac dosimetry metrics corresponded with worse OS.…”
Section: Discussionsupporting
confidence: 87%
“…In addition to the straightforward boost of statistical power granted by the increasing number of analyzed patients, which permitted us to obtain by the present study an unparalleled accuracy of the dose-response findings associated with RP of any grade. In particular, it is noteworthy that, despite the valuable independence of the dose values observed in the different substructures in the whole cohort (Figure 9), previously claimed interactions between the heart and the lungs in the RP development [38][39][40][41][42][43] are hereby confirmed. Indeed, we found, in the whole cohort, extended lung and heart regions in which the dose appears significantly correlated with the development of any-grade RP.…”
Section: Discussionmentioning
confidence: 64%
“…One hundred and six patients were treated at the Memorial Sloan Kettering Cancer Center of New York with stereotactic body RT (SBRT) for NSCLC. Patients received a median total dose of 50 Gy (range: [40,54] Gy) in median 4 fractions (range: [3,5]). Plans were designed in Eclipse v.13 (Varian Medical Systems, Palo Alto, CA, USA) using the AAA dose calculation engine.…”
Section: Stereotactic Body Radiation Therapymentioning
confidence: 99%
“…Some, but not all, of these reports suggested that minimizing the dose to the heart (“dose sparing”), particularly the upper regions of the heart, could improve RT-induced pneumonitis. One example involved evaluating the relationship between radiation doses to the heart and its substructures and pneumonitis during treatment for thymic epithelial tumors, because these tumors generally originate within the anterior mediastinal region and can spread into the pericardial space ( 25 ). This retrospective analysis indicated that RT-induced pneumonitis appeared despite the mean lung dose and lung V20 being lower than those used for locally advanced NSCLC, and that this seemed to be related to the dose (V35) to the pulmonary artery; the authors proposed that minimizing the dose to the pulmonary artery might reduce the incidence of pneumonitis in patients undergoing mediastinal RT.…”
Section: Management Of Radiation-induced Cardiopulmonary Toxicitiesmentioning
confidence: 99%